Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/infa.12021
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Parenting During Infancy: The Role of Infant Temperament and Marital Adjustment for Mothers and Fathers

Abstract: Although it is well accepted that parents greatly impact infant development, it is less clear which factors impact change in quantity and quality of parenting across infancy. This longitudinal study (N = 120 families) investigated how infant temperament and marital adjustment related to trajectories of mother and father involvement and sensitivity across infancy using multilevel models. Parental involvement (caregiving and play), infant temperament (surgency, negative affectivity, regulation), and marital adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
2
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 48 publications
(101 reference statements)
11
51
2
18
Order By: Relevance
“…Second, the finding that children high on surgency elicited greater maternal negative control but greater paternal positive support is consistent with previous studies showing that surgency can predict both positive and negative parenting Planalp et al, 2013). However, this pattern of results does not always emerge (e.g., see Lengua & Kovacs, 2005).…”
Section: Influence Of Child Temperamentsupporting
confidence: 88%
See 1 more Smart Citation
“…Second, the finding that children high on surgency elicited greater maternal negative control but greater paternal positive support is consistent with previous studies showing that surgency can predict both positive and negative parenting Planalp et al, 2013). However, this pattern of results does not always emerge (e.g., see Lengua & Kovacs, 2005).…”
Section: Influence Of Child Temperamentsupporting
confidence: 88%
“…For the present purposes, there was concern with the evocation of differential parental behavior due to child temperament. For example, infant surgency predicted decreased maternal sensitivity and caregiving behaviors but increased play behaviors (Planalp, Braungart-Rieker, Lickenbrock, & Zentall, 2013). In addition, found that adolescents high on Extraversion (analogous to surgency) elicited both parental warmth and overreactive discipline, suggesting that the role of surgency is quite complex.…”
Section: Introductionmentioning
confidence: 95%
“…More research is needed on these and other relevant factors to better understand the differences and similarities between the parenting behaviors of fathers and mothers. Because, as our study showed, mothers’ work demands are connected with paternal parenting behaviors, issues related to reconciliation between work and family are of special interest, like satisfaction with the division of labor (Phares et al 2009), marital satisfaction and support from the partner (Elam et al 2017; Planalp et al 2013). …”
Section: Discussionmentioning
confidence: 80%
“…Much less is known about the other two temperament factors in relation to sensitive parenting of infants. In the only study we found to report on this, higher infant surgency/extraversion was found to be associated with mothers’ lower sensitivity and orienting/regulation was not related to sensitivity (Planalp, Braungart-Rieker, Lickenbrock, & Zentall, 2013). …”
Section: Introductionmentioning
confidence: 91%